2003
DOI: 10.1063/1.1619563
|View full text |Cite
|
Sign up to set email alerts
|

Structuring nanodiamond cone arrays for improved field emission

Abstract: A structuring method capable of producing uniform, large-area cone arrays of diamond films was developed. The technique employs bias-assisted reactive ion etching and is applicable to any structure of diamond films ranging from microcrystalline to nanocrystalline. Variation of the etching conditions enables control of the cone density, geometry, and height. Surface nanostructuring of cone arrays significantly improves the field emission properties of diamond films of all kinds. The turn on field is reduced to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 23 publications
0
58
0
6
Order By: Relevance
“…In our experiments, the electrical field at the cone tip is 25 V / m at the voltage of 10 V between diamond cone and anode probe, which is determined using the equation 14 The emission current from the individual cone is about 1 ϫ 10 −2 A at 25 V/ m. The field enhancement factor ␤ for conical structure is expressed by 2.1͑h / r + 0.8͒ 0.73 , 15 and it is calculated as 325 for the present individual diamond cone when assuming the cone height of 5.1 m and cone apex radius R tip of 5 nm. At the same electrical field ͑25 V / m͒, Zhang et al reported an emission current density of about 10 2 mA/ cm 2 from single-crystal diamond cone arrays, 6 from which the emission current of a single diamond cone can be estimated as 5 ϫ 10 −4 A assuming a cone density of 2 ϫ 10 8 cm −2 . The present study indicates that the emission properties of individual diamond cone are greatly improved due to the exclusion of field shield effect.…”
Section: Z Cuimentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, the electrical field at the cone tip is 25 V / m at the voltage of 10 V between diamond cone and anode probe, which is determined using the equation 14 The emission current from the individual cone is about 1 ϫ 10 −2 A at 25 V/ m. The field enhancement factor ␤ for conical structure is expressed by 2.1͑h / r + 0.8͒ 0.73 , 15 and it is calculated as 325 for the present individual diamond cone when assuming the cone height of 5.1 m and cone apex radius R tip of 5 nm. At the same electrical field ͑25 V / m͒, Zhang et al reported an emission current density of about 10 2 mA/ cm 2 from single-crystal diamond cone arrays, 6 from which the emission current of a single diamond cone can be estimated as 5 ϫ 10 −4 A assuming a cone density of 2 ϫ 10 8 cm −2 . The present study indicates that the emission properties of individual diamond cone are greatly improved due to the exclusion of field shield effect.…”
Section: Z Cuimentioning
confidence: 99%
“…Zhang et al reported the FEE properties of diamond cone arrays formed by bias-assisted reactive etching process. 5,6 However, the FEE properties of individual diamond cone, which can present the intrinsic FEE properties of diamond cone due to the exclusion of field shield effect, have not been studied so far. Recently, a maskless technique using ion sputtering has been developed for the formation of sharp silicon cone arrays on porous silicon.…”
Section: Z Cuimentioning
confidence: 99%
“…As reported in ref. 95, the turn-on fields were 26.9, 6.2, 18.2, and 10.1 V μm −1 for the pristine flat nanocrystalline diamond film, a low-density nanocone array, a highdensity nanocone array, and an array of single-crystal diamond nanocones, respectively. The significant reduction of the turnon field by lowering the nanocone density from 10 8 cm −2 to 10 6 cm −2 is likely due to the elimination of the screening effect acting between adjacent emitters.…”
Section: D Structuresmentioning
confidence: 99%
“…14 shows the SEM image (Fig. 14a) of an array of diamond nanocones produced by plasma etching of nanosized grains 95 and the TEM image (Fig. 14b) detailing dimensions and single-crystalline nature of a single nanotip.…”
Section: D Structuresmentioning
confidence: 99%
See 1 more Smart Citation